An in vivo evaluation of the ontogeny of stereoselective fluoxetine metabolism and disposition in lambs from birth to one year of age. (2nd November 2019) - Chow, Timothy W.; Nguyen, Tuan-Anh; Riggs, K. Wayne; Rurak, Dan W.
Abstract: 1. The objective was to determine the ontogeny of stereoselective fluoxetine (FX) disposition in postnatal sheep from newborn to adulthood. 2. Catheters were implanted in a carotid artery and jugular vein. FX was administered intravenously, followed by serial arterial blood and cumulative urine collection. The concentrations of R, S -FX and R, S -norfluoxetine ( R, S -NFX) in samples were measured using a validated enantioselective LC/MS/MS analytical method. 3. The metabolism of FX at 4.2 ± 0.4 days was limited compared to adults, but had developed compared to the fetus. Total body clearance (ClTB ) did not significantly increase up to 33.6 ± 0.9 days, but significantly increased at 98.5 ± 2.0 days, with no further changes up to 397.3 ± 8.5 days. Up to 13.4 ± 0.8 days, the disposition of FX included Phase I metabolism to NFX and trifluoromethylphenol (TFMP), and renal elimination. At 32.9 ± 0.9 days, metabolism included Phase II conjugates of FX and NFX. Renal elimination of these compounds was low. 4. The elimination of FX increased in a non-linear manner during the first year in sheep. The metabolism and disposition of FX and NFX in plasma and urine were stereoselective and this appeared due to both stereoselective protein binding and metabolism.